Manfaat Penambahan Tiang Jaringan Guna Meningkatkan Komunikasi Digital di Jl. H.M. Yamin Kel. Sidodadi Kec.Medan Timur - Br Nasution, Najiah Maisaro; Siregar, Susilawati; Humaidi, Samir; Zidansyah, Arif; Simamora, Irma Yusriani (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information technology is the latest long wave of the socio-economic evolution of mankind by bringing changes in all lines of human life, including social, economic and political. The birth of digital communication has brought changes in people's behavior, including shifts in culture, ethics and existing norms. Research on information technology and social change has progressed significantly, ranging from speculative studies of its potential impact on social and economic life to detailed analysis of digital communications[1]. The discussion of digital communications and social change is part of the wider literature on innovation theory that began with Shannon's